2003
DOI: 10.1002/ajpa.10150
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum cortisol levels and mother‐infant interactions in Japanese macaques

Abstract: As evidence accumulates regarding the influence of hormones and stress-related conditions on maternal behavior, it becomes critical to better understand the relationship between physiological stress and the ability to cope with infants. Eight Japanese macaque females were observed 3 hr per week during the first 12 weeks after parturition; fecal samples were collected twice a week from each mother, starting 4 weeks before parturition and ending 4 weeks after parturition. Time spent in contact, maternal responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 42 publications
2
30
0
1
Order By: Relevance
“…After parturition, concentrations of fGC in the post-partum Amboseli females returned to the levels of cycling females (see also Beehner et al, 2006a; for similar decline in other primates see e.g. Bahr et al, 1998;Bardi et al, 2003;Ziegler et al, 1995). The marked individual differences we detected in fGC levels can arise from a range of genetic and ontogenetic sources that are beyond the scope of the present study; elucidating those will require a focused investigation in itself.…”
Section: Individual and Reproductive State Differences In Fgcsupporting
confidence: 49%
“…After parturition, concentrations of fGC in the post-partum Amboseli females returned to the levels of cycling females (see also Beehner et al, 2006a; for similar decline in other primates see e.g. Bahr et al, 1998;Bardi et al, 2003;Ziegler et al, 1995). The marked individual differences we detected in fGC levels can arise from a range of genetic and ontogenetic sources that are beyond the scope of the present study; elucidating those will require a focused investigation in itself.…”
Section: Individual and Reproductive State Differences In Fgcsupporting
confidence: 49%
“…Females with elevated postpartum urinary CORT spent less time in ventro-ventral contact with their infants and spent less time carrying and supporting their infants in a ventral position. In a study of the hormonal correlates of maternal behavior in Japanese macaques, Bardi et al (2003a) reported that females with high CORT levels were more likely to reject their infants than females with low CORT levels. Also, females with high CORT/E 2 ratios were more rejecting and responded to their distress calls more slowly, and they were less responsive to infants, than females with low CORT/E 2 ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Such socially mediated changes in CORT excretion might impact the expression of maternal caregiving behavior. In western lowland gorillas (Gorilla gorilla gorilla), postpartum CORT has been associated with reduced maternal responsiveness (Bahr et al, 1998), and in Japanese macaques (Macaca fuscata) postpartum CORT is associated with more rejecting mothering styles (Bardi et al, 2003a). Among human females, however, postpartum CORT has been positively associated with affectionate contact with infants (Fleming et al, 1997b), as well as maternal responsiveness to infant cues (Stallings et al, 2001).…”
Section: Study 2: Alloparental Assistance and Maternal Carementioning
confidence: 99%
“…This suggests that increased postpartum glucocorticoid concentrations may enhance maternal behavior or infant survivorship. The limited results from (captive) nonhuman primates are less clear [Bahr et al, 1998;Bardi et al, 2003Bardi et al, , 2004. Here we test the a priori hypothesis that high postpartum cortisol concentrations predict subsequent offspring survival, and evaluate whether the other fecal steroids are predictive of offspring survival.…”
Section: Steroid Hormones and Maternal Successmentioning
confidence: 98%